Bioactive glass S53P4 eradicates Staphylococcus aureus in biofilm/planktonic states in vitro - Torstein Grønseth; Lene K. Vestby; Live L. Nesse; Magnus von Unge; Juha T. Silvola (Upsala Journal of Medical Sciences, 2020)
Background: Increasing antimicrobial resistance to antibiotics is a substantial health threat. Bioactive glass S53P4 (BAG) has an antimicrobial effect that can reduce the use of antibiotics. The aim of this study was to evaluate the antimicrobial efficacy of BAG in vitro on staphylococci in biofilm and in planktonic form. Secondary aims were to investigate whether supernatant fluid primed from BAG retains the antibacterial capacity and if ciprofloxacin enhances the effect. Methods: BAG-S53P4 granules, <45 µm, primed in tryptic soy broth (TSB) were investigated with granules present in TSB (100 mg/mL) and after removal of granules (100, 200, and 400 mg/mL). The efficacy of BAG to eradicate Staphylococcus aureus biofilm in vitro was tested using 10 different clinical strains and 1 reference strain in three test systems: the biofilm-oriented antiseptic test based on metabolic activity, the biofilm bactericidal test based on culturing surviving bacteria, and confocal laser scanning microscopy (CLSM) combined with LIVE/DEAD staining. Results: Exposure to 48 h primed BAG granules (100 mg/mL) produced bactericidal effects in 11/11 strains (p = 0.001), and CLSM showed reduction of viable bacteria in biofilm (p = 0.001). Supernatant primed 14 days, 400 mg/mL, reduced metabolic activity (p < 0.001), showed bactericidal effects for 11/11 strains (p = 0.001), and CLSM showed fewer viable bacteria (p = 0.001). The supernatant primed for 48 h, or in concentrations lower than 400 mg/mL at 14 days, did not completely eradicate biofilm. Conclusion: Direct exposure to BAG granules, or primed supernatant fluid, effectively eradicated S. aureus in biofilm. The anti-biofilm effect is time- and concentration-dependent. When BAG had reached its full antimicrobial effect, ciprofloxacin had no additional effect.